The Effect of Sevoflurane Anesthesia on the Corneal Endothelium (Annals of Medical Research, 2021)
Aim: To evaluate the mean changes in corneal endothelial cells in eyes that operated under sevoflurane general anesthesia.
Keywords: General Anesthesia; Corneal Endothel; Sevoflurane.